Effects of a Specific Pre- and Probiotic Combination and Parent Stock Vaccination on Performance and Bacterial Communities in Broilers Challenged with a Multidrug-Resistant Escherichia coli - Laura Fuhrmann; Jürgen Zentek; Wilfried Vahjen; Ronald Günther; Eva-Maria Saliu (MDPI AG, 2022)
Antibiotic resistance poses a risk for human and animal health, leading to a growing demand for effective alternatives. Combining nutritional tools and parent stock vaccination could be an approach to achieve sufficient protection against bacterial infections in poultry. In an Escherichia coli O1/O18 challenge trial, we investigated the protective effects of feeding diets containing Enterococcus faecium DSM 7134 and fructooligosaccharides (FOS) combined with specific parent stock vaccination in 225 ROSS 308 broilers. Data on performance parameters, intestinal microbial composition and metabolites, and antibiotic resistance genes (sul1-3, dhfr1a, SHV-12) were obtained. E. faecium and FOS combined with parent stock vaccination led to the highest body weights, which were significantly higher than those of controls throughout the experiment and decreased the relative abundance of Proteobacteria in the crop digesta compared to that in the positive control. However, cumulative feed conversation remained unaffected by the strategies. Birds receiving the pre-/probiotic combination showed lower cecal pH levels and higher crop L-lactate concentrations than the controls, whereas copy numbers of dhfr1a (trimethoprim resistance) and SHV-12 (extended-spectrum beta-lactamase) genes were only decreased in broilers from vaccinated hens compared to those in the challenged control. In conclusion, prophylactic administration of E. faecium and FOS in combination with parent stock vaccination can have complementary effects by improving broiler weight gain and stimulating intestinal bacterial metabolism, which may be beneficial for maintaining gut health in terms of Escherichia coli infection.